POST-RADIATION POST-MASTECTOMY SYNDROME: ASPECTS OF EVIDENCE-BASED MEDICINE - M. P. Vavilov; Ye. V. Kizhayev; M. N. Kusevich (Опухоли женской репродуктивной системы)
Analysis of data from 136 patients with verified breast cancer treated with surgery and chemoradiotherapy revealed that radiotherapy adds to overall extent of post mastectomy lymphorrhea, increases the rate of lymphatic edema and renders unfavorable influence on the rate of recovery of disordered motor function of the humeroscapular region. Conclusion which can be drawn from analysis is the appropriateness of the term «post-radiation post-mastectomy syndrome».